Desain preparasi gigitiruan cekat mempengaruhi kesehatan jaringan periodontal - Edy Machmud (Journal of Dentomaxillofacial Science, 2008)
The main purpose of treating tooth with fixed restoration (crown or bridge) is to keephealthy the remaining tooth and their surrounding tissue. In order to provide theserviceability fixed partial denture in patient’s mouth, so the periodontal tissue shouldbe preserved so natural teeth used as abutment can be also maintained.